Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Melalui Metode Pembelajaran Aktif di Kelas V MI NW Bungtiang: Improving Students' Indonesian Language Learning Outcomes Through Active Learning Methods in Class V of MI NW Bungtiang - Saprudin Efendi; Irwan Yon Hadi; Siti Nurul Hudayana (Pendidikan Al-Gafari, 2025)
Learning a language is essentially learning to communicate. Indonesian language education is an important aspect that needs to be taught to students in schools. This study aims to improve the Indonesian language learning outcomes of fifth-grade students at MI NW Bungtiang through the application of active learning methods. This study used a quantitative approach with a quasi-experimental method and a classroom action research (CAR) design in two cycles. The subjects were all 17 fifth-grade students. The Power of Two type of active learning method was used in the learning intervention. Data collection techniques included observation and learning outcome tests. Data analysis was carried out through normality, linearity, homogeneity tests, and analysis of pretest and posttest results. The results showed a significant increase in student learning outcomes after the application of active learning methods. In addition, students showed increased participation, motivation, and enthusiasm in participating in the learning process. Thus, active learning methods have been proven effective in improving students' Indonesian language learning outcomes and can be a recommended learning strategy to be implemented at the elementary education level, especially in teaching Indonesian.